Determinan Kinerja Pegawai Ditinjau Dari Iklim Organisasi dan Budaya Organisasi (Studi Kasus Pada Kantor DLHK Kabupaten Mamuju) - Ferils, Muh (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
This research was conducted at the Department of Environment and Hygiene in Mamuju Regency, with the aim of knowing the influence of organizational climate and organizational culture on employee performance, both partially and simultaneously, as well as the most dominant correlation. This study uses a quantitative survey method approach, with a questionnaire tool distributed to respondents. Sampling used saturated sampling technique, the respondents of this study were all human resources with the status of 44 Civil Servants and 10 Employees with Employment Agreements, with a total of 54 respondents. Data management uses SPSS, the first data processing technique tests the quality of the research instrument using validity and reliability tests, the analytical tool used multiple linear regression, then to test the hypothesis using a partial test (t test), simultaneous test (F test), and to find out contribution correlation using the coefficient of determination (R2). The results of this study prove that organizational climate and organizational culture both partially and simultaneously have a significant influence on employee performance, then the correlation contribution value of organizational climate is 23.6% and organizational culture is 31.8 meaning that organizational culture is more dominant in influencing improvement the performance of the employees of the Mamuju Regency Environmental and Sanitation Office.